Farmer field school-IPM impacts on urban and peri-urban vegetable producers in Cotonou, Benin - Lund, T.; Sæthre, May-Guri; Nyborg, I.; Coulibaly, O.; Rahman, M.H. (Springer, 2010)
The use of synthetic pesticides among vegetable producers in urban and peri-urban Cotonou, Benin, has been increasing to the extent that certain insect pests have developed resistance to the pesticides. This paper assesses the impact of the farmer field school approach in an integrated pest management (IPM) project that aimed to increase IPM knowledge, adaptation/adoption of IPM options, and appropriate application of pesticides and awareness of related health hazards among vegetable producers in Cotonou. A sample of 54 semi-structured interviews was conducted with the vegetable producers, and a double difference model was used to compare the knowledge and practices before and after the project. The project led to increased knowledge about IPM, which was to some extent adapted into the participants' production systems, although no significant difference was noted for the type of synthetic pesticides used. The producers do adapt their practices when new technologies and practices emerge, but not always in ways that are environmentally sound or healthy.